Бактеріологічна оцінка якості норвезьких оселедців ”Norks Delikatesse” - Давиденко, Павло Олександрович; Davydenko, Pavel; Кулішенко, Олег Миколайович; Kulishenko, Oleg; Паскалова, Наталія Вікторівна; Paskalova, Natalija; Гапон, Лілія Вікторівна; Gapon, Lilija; Барнаш, Денис Сергійович; Barnash, Denis (Дніпропетровський ДАЕУ, 2017)
Наведено результати мікробілогічних досліджень норвезьких оселедців „ Norks Delikatesse” на предмет їх обсіменіння патогенною психрофільною мікрофлорою. Йєрсініози являють собою значну загрозу здоров’ю людей та тварин. Саме зберігання харчових продуктів, які не підлягають термічній обробці, кормів у холодильних камерах та сховищах неналежного санітарного стану та контакт їх з гризунами приводять до контамінації психрофілами та під час тривалого зберігання за низьких плюсових температур накопичення культур Yersinia pseudоtuberculosis та Yersinia enterocolitica, що стає причиною небезпечних. Recently, in Ukraine, there have been reports of cases of human suffering from infectious and invasive diseases due to the use of food products of inadequate quality. Over the past few years, only in the Dnipro and the region, cases of such dangerous diseases as botulism, trichinosis, salmonellosis, rota- and coronavirus infections have been reported. There are many reasons for this, including the crisis of the phytosanitary service, the development of spontaneous markets, the falsification of veterinary and sanitary examinations, the unsatisfactory state of the public catering and food trade places, the violation of the neighborhood of food products on the shelves of refrigerated cabinets and showcases. In the special medical and veterinary literature, little attention has been given to the problem of the sanitary evaluation of food products contaminated with psychrophilic pathogenic microorganisms and assessing the sanitary status of their storage locations (refrigerated cabinets, showcases, and refrigeration units). One of such dangerous zooantroponoses is pseudotuberculosis and intestinal yersiniosis, the causative agents of which Yersinia pseudotuberculosis and Yersinia enterocolitica, respectively, possess pronounced psychrophilia and reproduce well at the temperature of the refrigerator, and spread by contact of food products and packaging containers with rodents and soil. A significant role in the spread of these diseases is played also by pigs, who are carriers of these pathogens and contaminate with impurities the pigs of pastures and agricultural lands that are the cause of the appearance of these pathogens on vegetables and animal feeds. The need to conduct a microbiological study of fresh-salted, fresh-frozen herring "Norks Delikatesse", which is sold through the distribution network of Dnipro, is beyond doubt. Studying the morphological structure, cultural, biochemical properties of the pathogen causative agent from freshly frozen herrings "Norks Delikatesse", one can conclude that it is the causative agent of the pseudotuberculosis and it represents a significant sanitary hazard to the health of people and animals to which this pathogen will get into the diet with food and feed. Most likely, this pathogen got to the fish with tare boxes or refrigerators of ship holds, which were in contact with rodents, which are the natural reservoir of the causative agent of this infection. As a result of the carried out research of the sanitary quality of fresh-salted, fresh-frozen herring "Norks Delikatesse", bought in the supermarket chain of Dnipro, the culture of the dangerous pathogen Y. pseudotuberculosis was isolated, which can pose a real threat to the health of people and animals.
Bacteriology valuation of quality of norwegian "Norsk Delikatesse"
Keywords: норвезькі оселедці; norwegian herring; низька плюсова температура 3 °С; low positive temperature 3° С; гризуни; rodents; психрофільні патогенні мікроорганізми; psychrophilic pathogenic microorganisms; здоров’я людини; human health